2022
DOI: 10.1155/2022/6953166
|View full text |Cite
|
Sign up to set email alerts
|

A New Preparation Method for Peroral Endoscopic Myotomy in Patients with Achalasia Can Effectively Reduce the Esophageal Residual Contents: A Comparative Retrospective Study

Abstract: Background and Aim. After routine fasting for patients with achalasia before POEM (peroral endoscopic myotomy) procedure, solid contents may still remain in the esophagus. We aimed to compare the efficacy and patient satisfaction in patients with and without drinking large amounts of carbonated beverages preoperatively. Methods. This retrospective study enrolled 65 achalasia patients who underwent POEM from June 2017 to October 2021. Based on the preoperative diet strategies, patients were divided into carbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…6 A recent study reported that drinking carbonated beverages can reduce the duration of pre-operative endoscopy and improve the esophagus cleansing degrees comfortably and safely. 7 From this background, Yoon et al 8 evaluated the clinical usefulness of drinking warm water for the proper esophageal preparation before POEM. The warm water preparation was applied to 29 patients with achalasia before the POEM procedure.…”
mentioning
confidence: 99%
“…6 A recent study reported that drinking carbonated beverages can reduce the duration of pre-operative endoscopy and improve the esophagus cleansing degrees comfortably and safely. 7 From this background, Yoon et al 8 evaluated the clinical usefulness of drinking warm water for the proper esophageal preparation before POEM. The warm water preparation was applied to 29 patients with achalasia before the POEM procedure.…”
mentioning
confidence: 99%